Effects of Continuous Epidural Injection of Dexamethasone on Blood Glucose, Blood Lipids, Plasma Cortisol and ACTH in Patients With Neuropathic Pain - Liu, Xiao-hui; Du, Yu-min; Cong, Hai-jing; Liu, Guang-zhao; Ren, Yu-E (Frontiers in Neurology, 2021)
Objective: To study the effects of continuous epidural injection of dexamethasone on blood glucose, blood lipids, plasma cortisol, and adrenocorticotropic hormone (ACTH) in patients with neuropathic pain. Methods: Thirty patients with cervical spondylotic radiculopathy, lumbar disc herniation, herpes pain or postherpetic neuralgia were randomly divided into three groups and were treated with different doses of epidural injection of dexamethasone (Group S with a concentration of 25 μg/mL; Group M with a concentration of 50 μg/mL; Group L with a concentration of 100 μg/mL). Epidural catheterization placement was guided by computed tomography (CT), and was connected to the analgesic pump for 10 days. Visual Analog Score (VAS), fasting blood glucose (FBG), total cholesterol (CHOL), triglyceride (TG), 2 h postprandial blood glucose (2hPG) and the concentrations of cortisol, ACTH were measured before injection (T0), 2, 4, 6, 8, and 10 days during injection (D2, D4, D6, D8, D10), and 7, 14, 21, 28 days (W1, W2, W3, W4) after injection. Results: During and after the treatment, VAS score was significantly decreased, and group M and L had the lowest VAS score. The concentrations of cortisol and ACTH were significantly lower during the treatment, but all of them recovered to the normal level after stopping the injection. The treatment did not affect the CHOL and TG concentrations. Discussion: Epidural injection of dexamethasone at the concentration of 50 μg/mL is recommended for patients with neuropathic pain because of its good analgesic effect and less adverse effect on blood glucose, plasma cortisol, and ACTH.